IMPLEMENTAÇÃO DE AÇÕES DE EFICIÊNCIA ENERGÉTICA EM SISTEMA DE VAPOR DE UMA INDÚSTRIA FRIGORÍFICA - Benjamin Cunha do Amaral (2023)
The discovery in 1970 that oil is not an inexhaustible resource triggered the oil crisis, leading to an increase in price and scarcity of the product. This propelled discussions on energy efficiency and conservation at a global level. Brazil implemented energy efficiency incentive programs starting from the 1980s. The ecological footprint of humanity is monitored by the National Footprint and Biocapacity Accounts (NFAs), which reveals Earth Overshoot Day when human demand exceeds the planet's regenerative capacity. In the Brazilian industrial sector, although being the largest consumer of electric energy, there has not been a significant increase in consumption, indicating potential for improvement in energy management. There has been a decline in the generation of coal, nuclear, and natural gas-based energy, but sources such as solar, biomass, and wind energy have shown growth. Companies faced issues with raw materials and high costs during the pandemic, resulting in impacts on production chains. Specific actions for improvement in engines, pumps, compressors, and processes are implemented to address the increase in industrial energy consumption. Boilers in the food industry utilize a significant amount of fuel, making energy efficiency important for cost reduction. Research aims to optimize the steam system, bringing financial and environmental benefits to companies. A case study was conducted to investigate the energy efficiency of the steam generation system in a poultry processing plant. Bibliographic and field data were collected, including measurements of pressure, temperature, and wood consumption. The research employed a multidisciplinary approach and utilized quantitative methods. The objective was to propose measures to reduce steam consumption. The methodology was divided into six phases, including data collection, verification of the production process, and obtaining indicators. Goals were defined, and improvement actions were implemented based on the analyzed results. The Ishikawa Diagram was used to identify the root causes of the problem. The objectives of analyzing consumption and proposing energy efficiency actions in the steam system of a poultry processing industry were achieved, resulting in an 8.33% decrease in the kgComb/t indicator. The project demonstrated that significant fuel savings are possible, bringing environmental advantages and contributing to improving energy efficiency in industries utilizing steam systems.